2021
DOI: 10.1192/bjo.2021.45
|View full text |Cite
|
Sign up to set email alerts
|

Investigating smoking and nicotine dependence among people with severe mental illness during the COVID-19 pandemic: analysis of linked data from a UK Closing the Gap cohort

Abstract: Summary Smoking rates are higher for people who use mental health services, which contributes substantially to health inequalities. Smoking can lead to worse COVID-19 outcomes, yet it remains unclear whether smoking has changed for people who use mental health services. We examined smoking patterns in a large clinical cohort of people with severe mental illness, before and during the pandemic. We found high levels of nicotine dependence and heavier patterns of smoking. Although some people had reported quit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Almost half of the smokers in our cohort (49.1%) indicated that they had increased their consumption compared to the pre-pandemic situation, while only 8.8% indicated that they had decreased their consumption during the same period. These results are similar to those reported by Peckham et al [ 68 ] who analysed the smoking habits of 367 people with severe mental illness during the COVID-19 pandemic lockdown. Their results showed an increase in tobacco consumption in 54.5% of those surveyed, and a decrease in 12.1%.…”
Section: Discussionsupporting
confidence: 91%
“…Almost half of the smokers in our cohort (49.1%) indicated that they had increased their consumption compared to the pre-pandemic situation, while only 8.8% indicated that they had decreased their consumption during the same period. These results are similar to those reported by Peckham et al [ 68 ] who analysed the smoking habits of 367 people with severe mental illness during the COVID-19 pandemic lockdown. Their results showed an increase in tobacco consumption in 54.5% of those surveyed, and a decrease in 12.1%.…”
Section: Discussionsupporting
confidence: 91%
“…All of the included studies were published in 2021. A total of 45.5% ( n = 5) of the studies were conducted in Europe ( 31 , 33 , 34 , 37 , 40 ), while 36.4% ( n = 4) were conducted in the USA ( 32 , 35 , 38 , 42 ) and 18.2% ( n = 2) in Asia ( 39 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Across all studies, including cross-sectional and a few longitudinal designs, about 5–70% of the participants reported trying to quit or reduce tobacco use, or reported quitting altogether. 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Approximately 7–55% of participants increased use or relapsed, 46 , 47 , 48 , 51 , 53 , 54 , 55 , 56 and 14–93% of participants reported no change in tobacco use. 46 , 47 , 48 , 51 , 53 , 54 , 57 , 58 Importantly, although some studies have reported a decrease in the overall prevalence or amount of cigarette smoking during the pandemic, 59 , 60 others report no change in use frequency or even an increase in the number of cigarettes smoked per day 60 , 61 , 62 , 63 or an increase in the amount of other tobacco products used (eg, cigars, cigarillos).…”
Section: Tobacco Product Use Behaviours During the Pandemicmentioning
confidence: 99%